2021
DOI: 10.3390/ijms222212431
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor (AhR) Activation by 2,3,7,8-Tetrachlorodibenzo-p-Dioxin (TCDD) Dose-Dependently Shifts the Gut Microbiome Consistent with the Progression of Non-Alcoholic Fatty Liver Disease

Abstract: Gut dysbiosis with disrupted enterohepatic bile acid metabolism is commonly associated with non-alcoholic fatty liver disease (NAFLD) and recapitulated in a NAFLD-phenotype elicited by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in mice. TCDD induces hepatic fat accumulation and increases levels of secondary bile acids, including taurolithocholic acid and deoxycholic acid (microbial modified bile acids involved in host bile acid regulation signaling pathways). To investigate the effects of TCDD on the gut micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Specifically, bacterial-derived urease (cleaves urea into ammonia and carbon dioxide) ( 59 ) and deaminase ( 60 ) in the large intestine, and glutaminase activity in the small intestine ( 61 , 62 ) contribute to ammonia formation that accumulates in the portal circulation at levels ∼3 times higher than arterial blood ( 58 ). TCDD has been shown to disrupt the homeostasis of gut microbiota and metabolism in mice ( 63 , 64 , 65 , 66 ). Sustained hyperammonemia may be a direct consequence of low circulating acetyl-CoA levels, which is required for the formation of N-acetyl-glutamate, an essential urea cycle cofactor that allosterically regulates CPS1.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, bacterial-derived urease (cleaves urea into ammonia and carbon dioxide) ( 59 ) and deaminase ( 60 ) in the large intestine, and glutaminase activity in the small intestine ( 61 , 62 ) contribute to ammonia formation that accumulates in the portal circulation at levels ∼3 times higher than arterial blood ( 58 ). TCDD has been shown to disrupt the homeostasis of gut microbiota and metabolism in mice ( 63 , 64 , 65 , 66 ). Sustained hyperammonemia may be a direct consequence of low circulating acetyl-CoA levels, which is required for the formation of N-acetyl-glutamate, an essential urea cycle cofactor that allosterically regulates CPS1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Supplement of tryptophan derivatives IAAld or IAA, or treated with AhR activator Ficz obviously alleviated the liver injury induced by MCT. Notably, AHR activation by microbial tryptophan metabolites were shown to improve alcohol-related liver disease [ 15 ] and non-alcoholic fatty liver disease [ 40 ]. These evidence and current results highlight the association of tryptophan metabolites and AhR with liver damage for various causes, including the MCT-induced HSOS-like liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have reported an increased risk of developing cancers, nervous system degeneration, immune damage, thyroid disease, metabolic disorders, and reproductive and sexual development disorders in the general population as well as in subgroups such as Vietnam War veterans heavily exposed to dioxins [ 100 , 102 ]. With respect to liver health, TCDD (2, 3, 7, 8-tetrachlorodibenzo- p -dioxin), the most toxic dioxin, has been shown to alter blood and hepatic lipid levels, disrupt bile synthesis, impair the microbiome, and strongly contribute to NAFLD development and progression through the activation of aryl hydrocarbon receptor (AhR) [ 103 , 104 , 105 , 106 , 107 ]. Several other dioxins, including PCBs, have become a major concern for liver health, given their strong association with IR and NAFLD/NASH, especially under diet-inducing obesogenic conditions [ 86 , 108 , 109 , 110 , 111 ].…”
Section: Nutrition Environmental Pollutants and Nafldmentioning
confidence: 99%